Numerical simulations on periprosthetic bone remodeling: a systematic review. (June 2021) - Mirulla, Agostino Igor; Pinelli, Salvatore; Zaffagnini, Stefano; Nigrelli, Vincenzo; Ingrassia, Tommaso; Paolo, Stefano Di; Bragonzoni, Laura
Highlights: Femur and tooth were the most investigated bone segments. A bonded bone-implant interface was used in about half of the studies. 3D simulations were predominantly used. The bone remodeling function proposed by Huiskes et al. (1987) was used in more than half of the retrieved studies. The change in bone density was the most investigated outcome. Abstract: Background and objective: The aim of the present study was to review the literature concerning the analysis of periprosthetic bone remodeling through finite element (FE) simulation. Methods: A systematic review was conducted on 9 databases, taking into account a ten-year time period (from 2009 until 2020). The inclusion criteria were: articles published in English, publication date after 2009, full text articles, articles containing the keywords both in the abstract and in the title. The articles were classified through the following parameters: dimensionality of the simulation, modelling of the bone-prosthesis interface, output parameters, type of simulated prosthesis, bone remodeling algorithm. Results: Sixty-seven articles were included in the study. Femur and tooth were the most evaluated bone segment (respectively 41.8% and 29.9%). The 55.2% of the evaluated articles used a bonded bone-prosthesis interface, 73% used 3D simulations, 67.2% of the articles (45 articles) evaluate the bone remodeling by the bone density variation. At last, 59.7% of the articles employed algorithms based on a specific remodeling function. Conclusions: Increasing interest in the bone remodeling FE analysis in different bone segments emerged from the review, and heterogeneous solutions were adopted. An optimal balance between computational cost and accuracy is needed to accurately simulate the bone remodeling phenomenon in the post-operative period.